Pengaruh Social Media Marketing dan Word Of Mouth Terhadap Keputusan Pembelian Dengan Kualitas Produk Sebagai Variabel Moderasi Pada Toko Jims Honey 15A Kota Metro - Durotun Nasikah; Suwarto; Linda Agih Pradita (Universitas Muhammadiyah Metro, 2025)
This research aims to find out whether there is an influence of Social Media Marketing and Word of Mouth on purchasing decisions at the Jims Honey 15A Metro City Store. To find out product quality regarding purchasing decisions at the Jims Honey 15A Metro City Store. To find out and identify product quality that moderates the influence of consumer purchasing decisions at the Jims Honey 15A Metro City Store. This research uses quantitative research, the sample in this study was 100 people. Data collection techniques use questionnaires, data analysis uses Validity Test, Reliability Test, Normality Test, Linearity Test, Homogeneity Test, MRA Test, T Test, R Determination Test and Statistical Hypothesis Test. Using data processing program SPSS version 25. With results 1. Social media marketing has a positive effect on purchasing decisions. 2 Word of Mouth has a positive influence on purchasing decisions. 3. Social media marketing which is moderated by product quality variables has an acceptable value, has a positive effect on purchasing decisions. 4. Word of mouth which is moderated by the product quality variable has an acceptable value, has a positive effect on purchasing decisions.